Battle of the best friends - Dadey, Debbie (Dadey, Debbie. Mermaid tales, 2012)
Mermaid Echo is doing tail flips because she's going to see her favorite under-the-sea band, the Rays. They're performing for Pearl's birthday party and everyone at Trident Academy is invited except Echo's best friend Shelly.